The language of fashion - Roland Barthes; Andy Stafford (ed.); Michael Carter (ed.) (London: Bloomsbury, 2013)
"Roland Barthes was one of the most widely influential thinkers of the 20th Century and his immensely popular and readable writings have covered topics ranging from wrestling to photography. The semiotic power of fashion and clothing were of perennial interest to Barthes and The Language of Fashion - now available in the Bloomsbury Revelations series - collects some of his most important writings on these topics. Barthes' essays here range from the history of clothing to the cultural importance of Coco Chanel, from Hippy style in Morocco to the figure of the dandy, from colour in fashion to the power of jewellery. Barthes' acute analysis and constant questioning make this book an essential read for anyone seeking to understand the cultural power of fashion"--
Keywords: Costume; Clothing and dress; Fashion; Costume and personal appearence; Linguistics Semantics; Popular Culture; Philosophy Movements Structuralism; Social Sciences